Миниатюры средневековой рукописной книги как исторический источник - Киселева, Людмила («Նաիրի» հրատ.)
The present article is dedicated to the analysis of the miniatures in the manuscript "Reims Missal," kept in the National Library of Russia. It was created for the church of St. Nicaise of the Benedictine abbey in Reims. The date of the manuscript is determined and a detailed textual, codicological, paleographical research and the analysis of the illustrative material is carried on. Some miniatures reflect real facts of the Crusades. The Missal has a facsimile edition: Misal de Reims. Madrid: AyN Ediciones S.A., 2008.
Keywords: Источниковедение; Миниатюра; Средневековая рукопись